Oxidative Stress and Inflammation in First-Episode Psychosis: A Systematic Review and Meta-analysis. (28th August 2018) - Fraguas, David; Díaz-Caneja, Covadonga M; Ayora, Miriam; Hernández-Álvarez, Fabián; Rodríguez-Quiroga, Alberto; Recio, Sandra; Leza, Juan C; Arango, Celso
Abstract: Despite mixed findings, increasing evidence suggests that people with first-episode psychosis (FEP) show increased pro-inflammatory and pro-oxidative status. We used the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines to conduct a systematic literature search of cross-sectional studies comparing in vivo inflammatory and oxidative blood markers between FEP patients and healthy controls. We analyzed 61 independent samples from 59 publications, including 3002 patients with FEP (ie, patients with FEP, early psychosis, first-episode schizophrenia or early schizophrenia) and 2806 controls. After controlling for multiple comparisons, our meta-analysis showed that total antioxidant status and docosahexaenoic acid levels were significantly lower in FEP patients than in controls, whereas levels of homocysteine, interleukin-6 and tumor necrosis factor alpha were significantly higher in FEP patients than in controls. This suggests that FEP patients had reduced antioxidant status and a pro-inflammatory imbalance, and that these biological processes may be targets for managing FEP.